2016
DOI: 10.3109/14397595.2016.1160968
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-free treatment of tocilizumab monotherapy for microscopic polyangiitis: a single-arm, single-center, clinical trial

Abstract: TCZ monotherapy may be an alternative treatment strategy in some patients with MPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…TCZ (8 mg/kg) was administered at fortnightly intervals for the first 8 weeks (5 infusions) and then every 4 weeks for the next 40 weeks (10 infusions). Fortnightly infusions of TCZ were used to suppress the high disease activity of PMR as soon as possible, according to the dosage and administration for systemic juvenile idiopathic arthritis (JIA) or Castleman's disease, as previously described . An intense regimen of fortnightly infusions in the early phase of PMR is reasonable because the quality of life of most patients with PMR is substantially affected by the disease, although serum CRP levels are not as high as the levels observed in patients with JIA.…”
Section: Methodsmentioning
confidence: 99%
“…TCZ (8 mg/kg) was administered at fortnightly intervals for the first 8 weeks (5 infusions) and then every 4 weeks for the next 40 weeks (10 infusions). Fortnightly infusions of TCZ were used to suppress the high disease activity of PMR as soon as possible, according to the dosage and administration for systemic juvenile idiopathic arthritis (JIA) or Castleman's disease, as previously described . An intense regimen of fortnightly infusions in the early phase of PMR is reasonable because the quality of life of most patients with PMR is substantially affected by the disease, although serum CRP levels are not as high as the levels observed in patients with JIA.…”
Section: Methodsmentioning
confidence: 99%
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ]. A report showed that epidural administration of TCZ reduced pain due to sciatica with lumbar spinal stenosis [ 188 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…The use of concomitant GC is a significant risk factor for developing serious infections during TCZ treatment [39]. Therefore, based on our experience that TCZ monotherapy without GC and CYC led to the successfully remission of a patient with AAV complicated with RA, we conducted a prospective single-arm, singlecenter, cohort, pilot study on the efficacy of TCZ monotherapy for 7 MPA patients [40]. All patients received 8 mg/kg of intravenous TCZ biweekly for the first 2 months (5 courses), and monthly for the next 10 months (10 courses).…”
Section: Anca-associated Vasculitismentioning
confidence: 99%